(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2025)
Active blade-pitch and rotor-yaw control has allowed wind turbines to optimise power capture in low wind speeds and then limit loads, torque and power in high wind speeds. This has enabled larger rotor blades to be installed, which capture more energy. However, failures of the electric motor, gearbox or hydraulics employed by active pitch and yaw control mechanisms are unfortunately responsible for more wind turbine failures than any other subsystem. For the tidal industry, all but the smallest repairs must be carried out onshore. This requires expensive equipment, and relies upon suitable weather conditions and vessel availability, which can lead to costly delays. Tidal turbines must therefore be an order of magnitude more reliable than wind turbines if tidal energy is to become commercially viable, which means that failure-prone active pitch and yaw may not be the optimal solution for the industry. This study presents the development and testing of a novel two-bladed tidal turbine design which, for the first time, replaces both active blade-pitch and active yaw control with a passive mechanism. The two blades are mounted on bearings and coupled via pre-loaded springs. In low flow speeds the blades are held at their optimum angle. In high flow speeds, the blades pitch-to-feather as the hydrodynamic forces generated by the aft-swept blades induce a pitching moment at the root of each blade, replacing the function of active pitch to limit the loads generated by the rotor. Unlike winds, tidal currents are typically bi-directional, with the flood and ebb tides misaligned by only a few degrees. The novel design presented in this study features coupled blades which are free to rotate about a common pitch axis so that when the tidal current changes direction, both blades flip to face the oncoming flow. A hydrodynamic model of the turbine based on NREL’s AeroDyn blade element momentum code was coupled with a mechanical model of the passive pitch mechanism to predict the performance of the novel turbine design in quasi-steady conditions. The influence of blade geometry, spring stiffness, preload and friction were then analysed to assess their impact on the loads generated by the rotor in a range of operating conditions. This fed into the design of a concept which, for the first time, could be deployed to enable passive pitch at full-scale, in realistic flow conditions. A scale-model of the novel rotor hub design was built and mounted on a speed-controlled motor for tests at a range of current and rotor speeds in the tow tank at the University of Strathclyde’s Kelvin Hydrodynamic Laboratory. Rotor thrust and torque were measured using a load cell, while blade pitch angle was measured from high-speed camera footage. Tests demonstrated that the blades successfully flipped when the current changed direction, and measured thrust and torque agreed very closely with the numerical model, showing that a reduction in thrust of up to 35% compared to a rotor with fixed-pitch blades could be achieved. This validates the numerical model and demonstrates the benefits of the novel design.